1991
DOI: 10.1002/bjs.1800780316
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the diagnosis of acute appendicitis

Abstract: Ultrasonography with graded compression was performed in 525 patients with clinical signs of acute appendicitis. Of 207 patients with surgically proven appendicitis the inflamed appendix (diameter greater than or equal to 6 mm) had been visualized sonographically in 177 (86 per cent). The score for non-perforated appendicitis (91 per cent) was higher than for perforated appendicitis (55 per cent). Twenty-four patients in whom an inflamed appendix was seen on ultrasonography did not undergo surgery because of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
8

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 11 publications
2
45
0
8
Order By: Relevance
“…The criteria of AP diameter and wall thickness were suggested by R. Brooke Jeffery Jr [2,3] and his fi ndings were confi rmed by David H. Adams et al [4] and Ooms and Associates [5]. Wide variations in sensitivity, specifi city and positive predictive value of ultrasonography have been reported [6,7].…”
Section: Discussionmentioning
confidence: 96%
“…The criteria of AP diameter and wall thickness were suggested by R. Brooke Jeffery Jr [2,3] and his fi ndings were confi rmed by David H. Adams et al [4] and Ooms and Associates [5]. Wide variations in sensitivity, specifi city and positive predictive value of ultrasonography have been reported [6,7].…”
Section: Discussionmentioning
confidence: 96%
“…The first error leads to an unnecessary operation and the second to delay. 1 The existence of recurrent and chronic appendicitis is still doubted by many. A recent study of treatment of appendicitis presenting with antibiotics alone found that 95% resolve, but 35% represented with appendicitis within 17.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have shown that the overall accuracy of US in diagnosing acute appendicitis ranges between 87-96% (sensitivity 75-90%, specificity 86-100%) with positive and negative predictive values of 91-94% and 89-97% respectively [3,4,5,12]. In experienced hands US significantly improves diagnostic accuracy in suspected appendicitis while reducing the negative laparotomy rate to 8-15% [13].…”
Section: Discussionmentioning
confidence: 99%